The “TSH Receptor Glo Assay” – A High-Throughput Detection System for Thyroid Stimulation - Latif, Rauf; Lau, Zerlina; Cheung, Pamela; Felsenfeld, Dan P.; Davies, Terry F. (Frontiers in Endocrinology, 2016)
Background: To identify novel small molecules against the TSH receptor, we developed a sensitive transcription-based luciferase high-throughput screening (HTS) system named the TSHR-Glo Assay (TSHR-Glo). Methods: This assay uses double-transfected CHO cells stably expressing the human TSHR and a cAMP response element (CRE) construct fused to an improved luciferase reporter gene. Results: The assay was highly responsive towards TSH in a dose-dependent manner with a TSH sensitivity of 10-10M (10±1.12μU/mL) and thyroid-stimulating antibodies, a hallmark of Graves’ disease, could also be detected. The assay was validated against the standard indicator of HTS performance - the Z-factor (Z’) – producing a score of 0.895. Using the TSHR-Glo assay we screened 48,224 compounds from a diverse chemical library in duplicate plates at a fixed dose of 17μM. Twenty molecules with the greatest activity out of sixty-two molecules that were identified by this technique were subsequently screened against the parent luciferase stable cell line in order to eliminate false positive stimulators. Conclusion: Using this approach we were able to identify specific agonists against the TSH receptor leading to the characterization of several TSH agonist molecules. Hence, the TSHR-Glo assay was a one-step cell-based HTS assay which was successful in the discovery of novel small molecular agonists and for the detection of stimulating antibodies to the TSH receptor.